Tashas franchising : will service stand in the way of success? - Krost, Peta (SAGE knowledge. Cases., 2016)
It was a Saturday morning in April 2009 at Tashas at Atholl Square: the first Tashas that Natasha Sideris had opened, and her flagship store. As always, the restaurant was incredibly hectic. Sideris walked over to a table where one of the guests was complaining, and sought to smooth ruffled feathers. 'We waited half an hour for a table, and then the waiter got some of our drinks orders wrong! That's simply not acceptable!' Sideris apologised profusely, and gave drinks and dessert on the house to the party of four. This seemed to calm the customers down. But this complaint troubled Sideris, because it echoed similar incidents reported in the findings of recent customer service research at her restaurant. How should she move forward?